The persistent power of stigma: A critical review of policy initiatives to break the menstrual silence and advance menstrual literacy. - Mary M Olson; Nay Alhelou; Purvaja S Kavattur; Lillian Rountree; Inga T Winkler (Public Library of Science (PLoS), 2022)
Menstruation is shrouded in stigma and shame-that is the common refrain in burgeoning initiatives on menstrual health and hygiene. Public policies alone cannot undo stigma and enact social change, but they do interact with social norms. They can reflect and adopt stigmatizing attitudes and, as a result, institutionalize, formalize, and legitimize stigma; or they can actively challenge and denounce it and mitigate existing discrimination. Against this background, we explored whether and how policies on menstrual health and hygiene address menstrual stigma and advance menstrual literacy based on an analysis of 34 policy documents and 85 in-depth interviews with policy-makers and advocates in four countries: India, Kenya, Senegal, and the United States. We found that policies recognized menstrual stigma and set out to break the silence surrounding menstruation and advance menstrual education, but they did not contribute to dismantling menstrual stigma. Policy-makers seemed constrained by the very stigma they sought to tackle, resulting in hesitancy and missed opportunities. Policies raised awareness of menstruation, often with great noise, but they simultaneously called for hiding and concealing any actual, visible signs of menstruation and its embodied messiness. Educational initiatives mostly promoted bodily management and control, rather than agency and autonomy. As a result, policies might have succeeded in breaking the silence around menstruation, but stigma cannot be broken as easily. We first need to recognize its (invisible) power and its impacts in all spheres of life in order to actively challenge, dismantle, and redefine it.